Does Increasing the Supply of International Public Goods Reduce the Risk of WTO Complaints Against Member States? A Case Study of China - Gu, Xinyuan (International Journal of Social Sciences and Public Administration, 2024)
Kindleberger’s "International Public Goods Theory" posits a positive correlation between a nation’s power and its provision of international public goods. However, existing research does not address whether the supply of international public goods can reduce the risk of being sued in the WTO. This paper, through empirical analysis, concludes that increasing the supply of international public goods can reduce the risk of WTO complaints against member states. Conversely, reducing the supply of international public goods increases the risk of being sued in the WTO. China can reduce its risk of being sued in the WTO by increasing the supply of international public goods and building a consensus on international economic order.